Design of Algorithms for Implementation of Universal Asynchronous Receiver Transmitter - Sharma, Neha (My University, 2008)
Serial data communication is a somewhat tricky subject to approach, because one needs pieces of information from several places. Within a Microcomputer, data is transferred in parallel, because that is the fastest way to do it. For transferring data over long distances, however, parallel data transmission requires too many wires. Therefore, the data to be sent long distances is usually converted from parallel form to serial form so that it can be sent on a single wire or a pair of wires. Serial data received from a distant source is converted to parallel form so that it can easily be transferred on the Microcomputer buses. Serial data transmission can be synchronous or asynchronous. For synchronous transmission, the data is sent at constant rate, with denoted speed in bit/sec. In the field of aviation the data between the aircraft in the air and the controller at ground would never be a continuous stream. For this application asynchronous mode of transfer through a device UART is the most efficient way to go. In this work design of a UART using VHDL is presented. The simulation result on the baud, bit-rate are presented along with a review of history of navigation controls and matching of the designed UART with the aircraft receiver system.
ME(ECE)
Keywords: Uart; VHDL